COMMUNICATION STRATEGIES USED BY STUDENTS IN ENGLISH LEARNING ACTIVITIES - Debora Jesika Sihotang; Johannes Jefria Gultom; Mansyur Tarigan (Didaktika : Jurnal Pengabdian Masyarakat, 2026)
This study investigated students' communication strategies in English language learning at SMA Negeri 1 Percut Sei Tuan. The objectives of this study were to identify the types of communication strategies used by students and to describe how the strategies were applied during classroom interaction. This study employed a descriptive qualitative design. The participants were ten eleventh-grade students selected through purposive sampling. Data were collected through classroom observation and open-ended questionnaires distributed through Google Forms. The data were analyzed using the qualitative analysis procedures proposed by Miles, Huberman, and Saldaña, including data reduction, data display, categorization, interpretation, and conclusion drawing. The findings revealed five types of communication strategies based on Tarone's theory: avoidance strategy, paraphrase strategy, transfer strategy (code-switching), appeal for assistance strategy, and non-verbal strategy. Among these, transfer strategy was the most dominant strategy used by students. Furthermore, communication strategies were used to maintain interaction, convey intended meaning, avoid communication breakdown, support speaking fluency, and increase students' confidence during classroom interaction. The study concludes that communication strategies play an important role in helping students overcome speaking difficulties and participate actively in English learning activities.